Essential Oil Content and Composition of Different Parts (Stem, Leaf, Flower and Aerial Part) of Achillea filipendula Lam. - Sara Vojoudi; fatemeh sefidkon; Parvin Salehi; MH Salehi Sormaghi (Institue of Medicinal Plants, ACECR, 2018)
Background: Achillea filipendula Lam. is an aromatic and medicinal plant, green with hard and thick stem and 80-100 cm height in proper condition. Objective: In this research, for determining the proper plant part of Achillea filipendula for essential oil extraction, the seeds of this plant were collected from East Azerbayjan province and cultivated in Research Station of Alborz (Karaj). The oil percentage and chemical composition was studied in full flowering stage. Methods: The aerial parts of the plant were harvested in spring (2013). The essential oils of stem, leaves and flowers were extracted by hydro-distillation separately. The essential oil of total aerial parts was also obtained. The oils were analyzed by GC and GC/MS. Results: The results showed that the essential oil yields were 0.67% for flowers, 0.77% for leaves, 0.11% for stem and 0.6% for total aerial parts. Seventeen compounds were identified in the flower essential oil with santolina alcohol (18.5%), 1,8-cineole (26.2%), borneol (19.3%) and bornyl acetate (4.9%) as main components. Fifteen compounds were identified in the leaf essential oil with santolina alcohol (23.5%), 1,8-cineole (26.5%), borneol (19.1%) and bornyl acetate (6.3%) as major constituents. In the essential oil of stem, 13 components were characterized that neryl acetate (58.3%), spathulenol (7.4%) and globulol (3.4%) were the main components. Fifteen compounds were identified in aerial parts essential oil with santolina alcohol (20.6%), 1,8-cineole (33.7%), borneol (20.4%) and germacrene D (4.2%) as major constituents. Conclusion: All these parts of the plants contain essential oil, but with different yield and some difference and similarity in composition. It can be concluded that total aerial parts of Achillea filipendula are appropriate for distillation in spite of previous works that only flowers were used for obtaining essential oil.